Audiological evaluation of infants using mother's voice. (June 2019) - Saito, Osamu; Nishimura, Tadashi; Morimoto, Chihiro; Otsuka, Shintaro; Uratani, Yuka; Matsunaga, Yasuko; Hosoi, Hiroshi; Kitahara, Tadashi
Abstract: Objectives: Hearing loss is a serious problem in infants and children because it may interfere with the development of typical speech, verbal language, and auditory and communication skills. By measuring hearing ability (thresholds) as early as possible, even as early as during infancy, effective treatment can be administered. These treatments may significantly reduce the handicap associated with hearing loss. However, at times during behavioral auditory tests, observers cannot determine whether or not an accurate threshold was obtained. To support the use of infant audiometry for accurate diagnosis, audiologic behavioral responses may be obtained by selecting stimuli that interest infants, e.g., their mothers' voices. Methods: We evaluated 30 infants who were presented to our hospital for behavioral auditory assessment in 2016. The infants' ages ranged from 4 months to 3 years and 6 months. The mean age was 1 year and 10 months ±10 months (±standard deviation). The infants' hearing thresholds for their mothers' voices and warble tones at 250–4000 Hz were measured. Auditory brainstem response (ABR) had already been evaluated in 24 infants. Relationships between mother's voice and warble tone or ABR thresholds as well as responses to the initial stimuli and stimuli at the threshold were investigated. These responses were classified into four grades (no response, uncertain response, possible positive response, and positive response), and the response to mother's voice and warble tone were subsequently compared. Results: Mother's voice thresholds significantly correlated with all warble tone thresholds. In the relationship between the mother's voice threshold and average hearing levels of 500, 1000, and 2000 Hz, two infants were outliers. In these infants, the average hearing levels were relatively higher than the mother's voice thresholds. Judging from their ABR thresholds, the mother's voice thresholds were valid and the average hearing levels were worse than their original assessed hearing ability. The responses to mothers' voices were more distinct than those to warble tones, both for initial stimuli presentation and the determined threshold. Conclusions: Audiologic behavioral responses to mothers' voices were clearer than those for warble tones. Evaluations that use the mother's voice threshold are useful for estimating hearing levels in infants.